Tingkat Keterampilan Dasar Mengajar Calon Guru Sekolah Dasar Pada Perkuliahan Mikroteaching: Level of Basic Skills for Teaching Prospective Primary School Teachers at Mikroteaching Lectures - Yuanita, Yuanita (Pedagogia : Jurnal Pendidikan, 2019)
This research is a descriptive qualitative research purposes to identify the level of basic teaching skills of the prospective primary school teachers through microteaching subject and to find out the problems of basic skills mastery of the prospective primary school teachers in STKIP Muhamamdiyah Bangka Belitung. There are 5 basic skills assesed, include: 1) asking skills, 2) strengthening skills, 3) providing variaton skills, 4) explaining lesson skills, 5) opening and closing skills. The subject of this research is 42 college students in fifth semester who took microteaching subjects in academic year of 2018/2019 as sample. This research was conducted for 6 months and the research instruments were in the form of observation sheets and interviews. The identification results of basic teaching skills showed that 1) mean score of asking skills is 80.36, categorized as excellent, 2) mean score of strengthening skills is 84.23, categorized as excellent, 3) mean score of giving variaton skills is 77.20, categorized as excellent, 4) mean score of explaining lesson skills is 75.51, categorized as good, 5) mean score of opening and closing skill is 77.45, categorized as excellent. While, the problems that is faced to the prospective primary school teacher on mastering the basic teaching skills are feeling nervous, thoughtless materials, the teaching process is not based on lesson plan set, and students lack of practice.